Constitutional exclusion the rules, rights, and remedies that strike the balance between freedom and order - Tomkovicz, James J. (New York ; Oxford : Oxford University Press, 2011)
In this volume, James Tomkovicz discusses the 'exclusionary rules' which prevent evidence of a criminal defendant's guilt from being introduced at trial, and which incite strong, often hostile reactions from the public.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Due process of law -- United States; Criminal procedure -- United States; Constitutional law -- United States; Presumption of innocence -- United States; Burden of proof -- United States